Comparison of Antibacterial Activities of Ethanol and Methanol Extracts of Early Flower Leaves (Clitoria Ternatea L.) against Escherichia Coli ESBL (Extended Spectrum Beta Lactamase) - Susi Rahmawati; Ahwan Abdul; Fadilah Qonitah (Jurnal Jamu Indonesia, 2022)
Inappropriate use of antibiotics can lead to bacterial resistance. Extended Spectrum Beta Lactamase (ESBL) is a bacterium that is resistant to beta-lactam antibiotics such as penicillins, cephalosporins and monobactams. One example of this bacterium is Escherichia coli which can cause a number of diseases such as urinary tract infections, respiratory infections, sepsis and meningitis. The leaves of the telang flower (Clitoria ternatea L.) contain a number of compounds that have antibacterial activity which are expected to be an alternative for the treatment of infections caused by ESBL Escherichia coli. This study aims to determine the antibacterial activity of ethanol and methanol extract of telang flower leaves against Escherichia coli ESBL and to compare the activities of the two extracts. The test method is experimental, namely measuring the antibacterial activity of the extract using the disk diffusion method. The results of the phytochemical screening test conducted showed that the extract tested positive contained flavonoids, alkaloids, phenolics, saponins, tannins and terpenoids. The results of the research related to the antimicrobial activity of the concentrations of 25%, 50% and 100% methanol extract produced inhibition zone diameters of 7.4 mm, 7.8 mm and 8.1 mm, while the ethanol extracts were 7.3 mm, 7.4 mm. , 7.9 mm. The positive control used, namely gentamicin, produced an inhibition zone of 9.8 mm. These results indicate that the methanol and ethanol extract of telang flower leaves affected the growth of Escherichia coli ESBL and there was a difference in the antibacterial activity of the two extracts based on statistical analysis with the Anova test with p value <0.05.